Emergency surgical stent retrieval following stent dislodgement during ductal stenting for hybrid palliation. (19th February 2021) - Tongut, Aybala; Desai, Manan; Peer, Syed Murfad; Yerebakan, Can
Abstract: Stenting of the ductus arteriosus is part of the hybrid treatment of high-risk patients with hypoplastic left heart syndrome. Dislodgement of a ductal stent is a rare complication. We present challenges faced in successful surgical retrieval of a dislodged ductal stent in a high-risk infant undergoing hybrid palliation for hypoplastic left heart syndrome.